Sustainability Status of Bale Tani Vernacular Architecture in Sade Village, Central Lombok Regency, West Nusa Tenggara - Ramadhan, Muhammad Hafizh; Nugroho, Agung Murti; Asikin, Damayanti (Fakultas Teknik Universitas Brawijaya, 2024)
Sade Village displays a unique settlement pattern that is influenced by geographical conditions and the needs of its residents. One of the buildings that follows the contour of Sade Village is Bale Tani, a medium-sized bale generally inhabited by families with a middle economic level. Bale Tani has undergone several changes due to the wishes of its residents, which have the potential to influence the sustainability of its vernacular architecture. This research aims to analyze the sustainability of Bale Tani vernacular architecture in Sade Village using the Multidimensional Scaling (MDS) method through the RAPFISH application, as well as carry out leverage analysis to identify indicators that influence sustainability. The results of the analysis show that the overall level of sustainability of the Bale Tani vernacular architecture is less than satisfactory, with a sustainability index value reaching 47.64%. Each of the analyzed dimensions, such as visual image, climate responsiveness, and comfortable living space, shows a low level of sustainability. Of the 18 indicators observed, nine indicators, including kamar dedare, kamar dengan to’aq, roof sheathing, wall sheathing, window openings, building floor, floor plan, roof, and wall, are the dominant factors in the sustainability of Bale Tani vernacular architecture.